Answer:
C. (-1, 2)
Explanation:
The midpoint has coordinates that are the average of the endpoint coordinates. If the endpoints are A and B, and the midpoint is M, the equation for this is ...
M = (A+B)/2
Solving for B, we get ...
2M = A + B
2M - A = B
This tells us we can find the other endpoint by subtracting the coordinates of the given endpoint from twice the midpoint coordinates. (It is useful to remember this.)
B = 2(1, -2) - (3, -6) = (2-3, 2(-2)-(-6)) = (-1, 2)
The other endpoint is (-1, 2).
_____
You can also graph the points and find one as far from center as the given endpoint is.